2006
DOI: 10.1158/0008-5472.can-06-2020
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p63 Leads to Increased Cell Migration and Up-regulation of Genes Involved in Invasion and Metastasis

Abstract: Abstractp63, a homologue of the tumor suppressor p53, is critical for the development and maintenance of squamous epithelia. p63 is specifically expressed in the basal layers of stratified epithelial tissues and is considered a specific marker for cells of this type. The role of p63 in tumorigenesis remains poorly defined. Numerous studies have highlighted the oncogenic potential of the predominant p63 isoform #Np63A; however, data suggest that other p63 proteins can act as tumor suppressors or alter the metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
190
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(213 citation statements)
references
References 47 publications
(70 reference statements)
21
190
2
Order By: Relevance
“…We previously showed that ΔNp63α inhibits cancer cell migration, invasion, and metastasis by upregulating expression of the metastasis suppressor CD82, a member of the tetraspanin family of proteins (47), as well as MAP kinase phosphatase 3 (MKP3), which negatively regulates Erk2 signaling to inhibit cancer cell migration, invasion, and metastasis (45). In addition, ΔNp63α has been shown to regulate N-cadherin, L1 adhesion molecule, and Wnt-5A, which play a role in regulating cell migration (65), and to repress cell invasion by inhibiting Ets-1-mediated matrix metallopeptidase 2 (MMP2) expression via Id-3 up-regulation (66). Hence, ΔNp63α may act as a master regulator in regulation of cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that ΔNp63α inhibits cancer cell migration, invasion, and metastasis by upregulating expression of the metastasis suppressor CD82, a member of the tetraspanin family of proteins (47), as well as MAP kinase phosphatase 3 (MKP3), which negatively regulates Erk2 signaling to inhibit cancer cell migration, invasion, and metastasis (45). In addition, ΔNp63α has been shown to regulate N-cadherin, L1 adhesion molecule, and Wnt-5A, which play a role in regulating cell migration (65), and to repress cell invasion by inhibiting Ets-1-mediated matrix metallopeptidase 2 (MMP2) expression via Id-3 up-regulation (66). Hence, ΔNp63α may act as a master regulator in regulation of cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, beyond its dominantnegative effect on p53 suppressor function, DNp63 was found to favour angiogenesis and chemoresistance (Senoo et al, 2002;Wu et al, 2005;Rocco et al, 2006) and to regulate cell-adhesion processes (Carroll et al, 2006;Yang et al, 2006). Conversely, several studies reported a loss of p63 expression in metastatic stages (Barbieri et al, 2006;Adorno et al, 2009). These observations suggest a dual role of DNp63 in tumourigenesis with enhanced expression in the early stages of progression during which the epithelial cell fate is maintained, followed by loss of expression when cells acquire mesenchymal properties associated with metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Third, downregulation of p63/p73 in p53-null MEFs stimulated DNA synthesis and transformation potential to levels similar to those in mutant p53 MEFs (Lang et al, 2004). It is relevant that loss of p63 has been recently shown to upregulate genes involved in invasion and metastasis (Barbieri et al, 2006). This could in part explain the reasons for the increased metastasis observed in mice expressing mutant p53.…”
Section: Mutant P53 Interactions With P63 and P73 Have Functional Outmentioning
confidence: 92%